The Falklands Conflict – History and Predictions for The Future - Marek Bodziany; Anna Kotasińska (Historia i Polityka, 2018)
The key focus of the article is the conflict over the Falkland Islands – a corner of the world that has been disputed for centuries due to its unique geographical location and rich natural resources. While the location factor had been the source of antagonism between Argentina and the United Kingdom since the 19th century already, the second element is relatively new; the most relevant discoveries were made only in the late 20th century. Experiences gained from the short, but very costly conflict of 1982 show that the Falklands crisis has not been completely resolved, and the threat of outbreak of a new conflict over the Islands in the future is real.